Healing of venous ulcers secondary to an ankle arteriovenous fistula - Liew, Ngoh Chin; Lee, Limi; Gee, Tikfu; Jabar, Mohd Faisal (Elsevier, 2015)
Venous ulcer as a complication of ankle arteriovenous fistula for hemodialysis is rarely reported. It poses a challenge between ulcer healing and fistula preservation. We report our experience in the management of venous ulcers secondary to an ankle arteriovenous fistula in a hemodialysis patient.